Activity of lenalidomide in mantle cell lymphoma can be explained by NK cell‐mediated cytotoxicity. (2nd August 2017) - Hagner, Patrick R.; Chiu, Hsiling; Ortiz, Maria; Apollonio, Benedetta; Wang, Maria; Couto, Suzana; Waldman, Michelle F.; Flynt, Erin; Ramsay, Alan G.; Trotter, Matthew; Gandhi, Anita K.; Chopra, Rajesh; et al.
Summary: Lenalidomide is an immunomodulatory agent that has demonstrated clinical benefit for patients with relapsed or refractory mantle cell lymphoma (MCL); however, despite this observed clinical activity, the mechanism of action (MOA) of lenalidomide has not been characterized in this setting. We investigated the MOA of lenalidomide in clinical samples from patients enrolled in the CC‐5013‐MCL‐002 trial (NCT00875667) comparing single‐agent lenalidomide versus investigator's choice single‐agent therapy and validated our findings in pre‐clinical models of MCL. Our results revealed a significant increase in natural killer (NK) cells relative to total lymphocytes in lenalidomide responders compared to non‐responders that was associated with a trend towards prolonged progression‐free survival and overall survival. Clinical response to lenalidomide was independent of baseline tumour microenvironment expression of its molecular target, cereblon, as well as genetic mutations reported to impact clinical response to the Bruton tyrosine kinase inhibitor ibrutinib. Preclinical experiments revealed lenalidomide enhanced NK cell‐mediated cytotoxicity against MCL cells via increased lytic immunological synapse formation and secretion of granzyme B. In contrast, lenalidomide exhibited minimal direct cytotoxic effects against MCL cells. Taken together, these data provide the first insight into the clinical activity of lenalidomide against MCL, revealing a predominately immune‐mediated MOA.